Review of Security Cooperation Mechanisms Combatant Commands Utilize to Build Partner Capacity - Moroney, Jennifer D. P. (RAND Corporation, 2013)
Security cooperation is an important instrument of the U.S. government for advancing national security objectives vis-à-vis allies and partner countries. This report characterizes security cooperation mechanisms for capacity-building, produces a detailed database of the mechanism elements, develops and applies a preliminary means of evaluating select mechanisms, and recommends ways to improve mechanism effectiveness and efficiency.